Beyond Accuracy: The Essential Contribution of Text Function to Translation Quality Assessment - Rudy Sofyan; Rusdi Noor Rosa; Bahagia Tarigan (Jurnal Arbitrer, 2026)
The growing diversity of translation quality assessment (TQA) models has raised concerns about consistency and reliability, as previous studies show that the same target text may receive different quality judgments when evaluated using different frameworks. This variation exposes the limitations of accuracy-oriented approaches and underscores the need for a more function-sensitive assessment model. In response, the Function-Based TQA model introduces text function as a key quality dimension that extends evaluation beyond linguistic correctness to communicative effectiveness. This study examines the importance of incorporating text function as a central criterion in TQA and explores its perceived role among translation professionals. Adopting a descriptive research design, the study draws on qualitative data from questionnaires and semi-structured interviews with translation lecturers and professional translators actively engaged in TQA. The data were analyzed using an interactive qualitative data analysis model. The findings demonstrate that text function plays a fundamental role in TQA by determining whether the target text fulfills the same communicative purpose as the source text within its target context. To facilitate practical assessment, this study proposes clearly defined quality descriptions and a corresponding scoring system for different levels of functional adequacy. Overall, the study argues that including text function as a distinct quality dimension enhances the consistency, explanatory power, and applicability of TQA models, contributing to a more holistic approach to translation evaluation.